Disaster Preparedness and the Abeyance of Agency: Christian Responses to Tropical Cyclone Winston in Fiji. Issue 1 (2nd April 2020) - Cox, John; Varea, Renata; Finau, Glenn; Tarai, Jope; Kant, Romitesh; Titifanue, Jason; Neef, Andreas
ABSTRACT: International practices of disaster preparedness presume human agency, particularly at the household level, as an important pre-emptive response to anticipated natural hazards. Our analysis of Fijian responses to Tropical Cyclone Winston indicates that preparedness is also regarded as important by cyclone survivors but has a moral dimension that can be used to assign blame to underprepared members of the community. However, Fijian villagers' experiences of terror and awe during Tropical Cyclone Winston also make them aware of the limits of human agency, prompting them to reflect on God's role in the cyclone and the need for collective repentance and renewed Christian commitment. The effectiveness of disaster preparedness and climate change adaptation efforts can only be enhanced by a better understanding of the values of affected communities, including religious and spiritual values. We seek to contribute to this knowledge by showing how disaster preparedness both converges with and diverges from Fijian Christian practices.